Literature Matters - Hillis Miller, J. (Open Humanities Press, 2016)
This new collection of J. Hillis Miller's essays centres on the question "why and to what end should we read, teach, and spend our time with literary and/or cultural studies?" At a time when electronic media seem to dominate the market completely, and jobs follow the money flows into electronic and technical fields, literary and cultural studies might appear as a decorative addenda but not really necessary for the process of growth and development, neither in business nor in the area of personal development. This question is not really new, it has many facets, requires differentiated answers which depend and mirror the political and cultural climate of a society.